Dynamic copy choice: Steady state between murine leukemia virus polymerase and polymerase-dependent RNase H activity determines frequency of in vivo template switching - Hwang, Carey K. (The National Academy of Sciences, 2001)
We recently proposed a dynamic copy-choice model for retroviral recombination in which a steady state between the rates of polymerization and RNA degradation determines the frequency of reverse transcriptase (RT) template switching. The relative contributions of polymerase-dependent and polymerase-independent RNase H activities during reverse transcription and template switching in vivo have not been determined. We developed an in vivo trans-complementation assay in which direct repeat deletion through template switching reconstitutes a functional green fluorescent protein gene in a retroviral vector. Complementation in trans between murine leukemia virus Gag-Pol proteins lacking polymerase and RNase H activities restored viral replication. Because only polymerase-independent RNase H activity is present in this cell line, the relative roles of polymerase-dependent and -independent RNase H activities in template switching could be determined. We also analyzed double mutants possessing polymerase and RNase H mutations that increased and decreased template switching, respectively. The double mutants exhibited low template switching frequency, indicating that the RNase H mutations were dominant. Trans-complementation of the double mutants with polymerase-independent RNase H did not restore the high template switching frequency, indicating that polymerase-dependent RNase H activity was essential for the increased frequency of template switching. Additionally, trans-complementation of RNase H mutants in the presence and absence of hydroxyurea, which slows the rate of reverse transcription, showed that hydroxyurea increased template switching only when polymerase-dependent RNase H activity was present. This is, to our knowledge, the first demonstration of polymerase-dependent RNase H activity in vivo. These results provide strong evidence for a dynamic association between the rates of DNA polymerization and polymerase-dependent RNase H activity, which determines the frequency of in vivo template switching.